THE LANGUAGE STYLE IN THE LYRICS OF DARA AYU'S SONG AND ITS LEARNING IMPLICATIONS - Anwar, Syamsul; Nirmala, Afsun Aulia (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2020)
Literature is an art form expressed by human thoughts and feelings with the beauty of language, the authenticity of ideas, and the depth of messages. instruction "or" guideline ", from the basic word Å›Äs- which means" instruction "or" teaching ". Language style in rhetoric is known as style. In subsequent developments, the word style then changed to the ability and expertise to write or use words The results of lyric research on Dara Ayu's songs can be concluded that there is a dominant language style that is asonance, and there are other styles of language, for example personification, repetition and parallelism.Keywords: language style, song lyrics, implications